Pelatihan Digital Marketing Pelaku Usaha Kecil Jemaat Gmim Kharisma Buha Kecamatan Mapanget - Robby Tanod Mamusung; Willem Gilbert Pomantow (Syntax Corporation Indonesia, 2025)
The Digital Marketing Training for small business actors in GMIM Kharisma Buha, Mapanget District, aims to enhance marketing technology understanding among local entrepreneurs. This study identifies that many small business owners have not maximized their utilization of digital technology following the COVID-19 pandemic. Through this training, participants were introduced to the use of social media platforms like Instagram and Google Maps to promote their products. The training results indicate a significant improvement in digital skills, enabling business actors to enhance their visibility and product sales. This program is expected to continue supporting the development of SMEs in the area..